Assessing InsurTech Purchase Intentions Among Young Working Adults in Malaysia: A TRA Approach - Mohd Rom, Noor Ashikin; Abdul Malek Beh, Nur Hidayah; Abdul Rani, Nazatul Shima; Md. Hassan, Nurbani; Agos Lokman, Farha Zafira (Society of Visual Informatics, 2025)
InsurTech is emerging as a key player in Malaysia's insurance landscape, bolstered by strong government support, regulatory initiatives, and increasing consumer demand for digital solutions. As the insurance industry undergoes digital transformation, understanding the factors driving the adoption of InsurTech platforms is crucial for both academic inquiry and industry practice. This study aims to investigate the factors influencing young working adults' intentions to purchase life insurance using InsurTech platforms. Utilizing a quantitative approach based on the Theory of Reasoned Action (TRA), the research gathered data from 118 respondents through a non-probability convenience sampling method, which was then analyzed using SPSS version 29 and multiple linear regression. The findings indicate that attitude, subjective norms, insurance literacy, and trust have significant and positive effects on the intention to purchase life insurance via InsurTech platforms among Malaysian young working adults. Notably, attitude and trust emerged as the most influential factors, highlighting the transformative role of technology in shaping consumer behavior. These results, along with broader industry trends, emphasize the growing importance of InsurTech in the insurance sector, particularly in driving purchase intentions among younger demographics. To stay competitive, insurers must focus on fostering trust and enhancing the perceived value of their digital platforms. The rapid integration of AI, IoT, and other advanced technologies not only streamlines operations and reduces costs but also enhances customer experience, ensuring that InsurTech will remain central to the industry's future. For future research, investigating the impact of emerging technologies such as blockchain and AI on trust and customer experience within InsurTech platforms would be a promising direction.